AMINO ACID SENSING PATHWAYS IN INFLAMMATORY BOWEL DISEASE. (22nd January 2022) - Solanki, Sumeet; Lee, Jun-Hee; Shah, Yatrik
Abstract: IBD is a chronic inflammatory disease of the gastrointestinal tract affecting millions of people worldwide. The last few decades have seen rapid increase of IBD cases in the US contributing to exorbitant health-care costs and morbidity rates. IBD comprises of two major subtypes: ulcerative colitis and Crohn's disease. Although the etiology of IBD is not completely understood, a complex interaction of environmental, genetic, immune, and gut microbial factors contributes to its pathogenesis. These factors ultimately converge to disrupt intestinal epithelial cell homeostasis, compromising mucosal barrier function, leading to unresolved relapsing inflammatory injury. Poor dietary habits such as Western diet are thought to play a pivotal role in the development of colitis. A healthy and balanced diet is important in management of the disease. Epidemiological and experimental studies demonstrate that high-protein diet triggers inflammatory flares and colitis patients are often advised to reduce animal dietary protein. However, colitis patients are also at high risk of a protein malnutrition. Thus, the precise mechanisms by which low dietary protein increases incidence of colitis and/or aggravate already established disease remains unknown. Our preliminary findings suggest that low dietary protein intake aggravated dextran sulfate sodium (DSS)-induced colitis with reduced body weight, colon length and increased histological injury. Dietary habits impact intestinal epithelial cell homeostasis and regeneration process in the event of an injury. The mechanistic target of rapamycin complex 1 (mTORC1), a 'master' regulator of cell growth participates in intestinal tissue regeneration. Remarkably, studies inhibiting mTORC1 activity have shown to disrupt the regenerative capacity of intestinal epithelium and increased susceptibility to colitis while activating mTORC1 had a positive effect. As amino acids potently activate mTORC1, we assessed and found that low dietary protein significantly reduce colonic mTORC1 activation. The newly discovered GAP activity towards Rags (GATOR1 & GATOR2) complexes act as amino acid sensing pathways by which mTORC1 activity is modulated. GATOR1 is a negative regulator, whereas GATOR2 is a positive regulator of mTORC1. CRISPR/CAS9 knockout of Wdr24 (GATOR2) led to inactivation of mTORC1 under amino acid culture conditions. Next, we investigated the role of amino acid sensing pathway in colitis models and found that disruption of intestinal epithelial specific GATOR2 complex (Wdr24 ΔIE ) attenuated mTORC1 activity and increased susceptibility to colitis. These findings suggest that low protein diet impacts colitis by modulating the intestinal epithelial amino acid sensing pathway.